Microwave-assisted sol-gel synthesis of TiO2-mixed metal oxide nanocatalyst for degradation of organic pollutant - Imoisili, Patrick Ehi; Jen, Tien-Chien; Safaei, Babak (De Gruyter Poland Sp Z O O, 2021)
Titanium dioxide (TiO2) is the most effective photocatalysts for low-cost degradation of organic pollutant; however, the wide band gap and the high recombination rate of the charge carriers are drawbacks that hinders it practical application. In this study, TiO2 and titanium mixed metal oxides ternary (V/Ag/TiO2) nanocatalyst was synthesized through a microwave-assisted sol-gel route using Ti (C4H9O)(4), NH4VO3, and AgNO3 as precursors. The XRD analysis of the synthesized TiO2 and V/Ag/TiO2 depicts lattice fringes for rutile and anatase crystalline phases. Raman spectra indicate the formation of a mesoporous multiphase sample mixture of rutile and anatase phases. The spectrum shift to the visible light region was demonstrated by the UV-visible spectroscopy analysis. Diffuse reflectance spectroscopy (DRS) reveals a reduced band gap of 2.9 eV for TiO2 and 2.65 eV for V/Ag/TiO2. Brunauer-Emmett-Teller (BET) indicates a large surface area of 92.8 and 84.8m(2) g(-1) for TiO2 and V/Ag/TiO2, respectively. Nitrogen adsorption-desorption isotherm exhibits type IV isotherm, signifying the presence of the mesoporous structure. SEM portrays a cluster of rod-like aggregate particles, while the HRTEM analysis illustrates nanoparticles of rod-like cylindrical shape with a homogeneous size diameter. The synthesized nanocatalyst demonstrated a significant photocatalytic ability in the degradation of methyl orange (MO) and methylene blue (MB). V/Ag/TiO2 shows higher activity in the visible region. Thus, the present report suggests efficient, suitable, and economical microwave-assisted sol-gel techniques to yield V/Ag/TiO2 nanocatalysts with harnessed photocatalytic performance for the degradation of toxic organic pollutants in the presence of visible light irradiation.
Keywords: microwave; mixed metal oxide; nanocatalyst; sol-gel; photocatalysis